Hi!(adsbygoogle = window.adsbygoogle || []).push({});

I tried to compute an ideal barbell-shaped object's dynamics, but my results were wrong.

My Langrangian is:

## L = \frac{m}{2} ( \dot{x_1}^2 + \dot{x_2}^2 + \dot{y_1}^2 + \dot{y_2}^2 ) - U( x_1 , y_1 ) - U ( x_2 , y_2 ) ##

And the constraint is:

## f = ( x_1 - x_2 )^2 + ( y_1 - y_2 )^2 - L^2 = 0 ##

I dervated L + λf by ## x_1, x_2, y_1, y_2 ## and λ:

## m \ddot x = - \frac{\partial U}{\partial x_1 } + \lambda ( x_1 - x_2 ) ## (1)

Four equtions similar to this and the constraint.

Then I expressed ## \ddot x_2 , \ddot y_1 , \ddot y_2 ## with ## \ddot x_1 , x_1 , x_2 , y_1 , y_2 ## and U's partial derivates' local values:

## m \ddot x_2 + \frac{\partial U}{\partial x_2} = - m \ddot x_1 - \frac{\partial U}{\partial x_1} ##

## m \ddot y_2 + \frac{\partial U}{\partial y_2} = - m \ddot y_1 - \frac{\partial U}{\partial y_1} ##

## ( m \ddot y_1 + \frac{\partial U}{\partial y_1} )(x_1 - x_2) = (- m \ddot x_1 - \frac{\partial U}{\partial x_1})(y_1 - y_2) ## (2)

After expressing ## (x_1 - x_2) , (y_1 - y_2) ## and ## \lambda ## from equation (1) and (2), substituted it into the constraint eqution I got an equation like this:

## (m \ddot x_1 + \frac{\partial U}{\partial x_1} ) * <something> = 0 ##

I think it's wrong.

Can you confirm or point on my mistake?

Thanks :)

**Physics Forums - The Fusion of Science and Community**

# Constrained Lagrangian equetion (barbell)

Have something to add?

- Similar discussions for: Constrained Lagrangian equetion (barbell)

Loading...

**Physics Forums - The Fusion of Science and Community**